The Effect of pH and Aging Time on the Synthesis of TiO2 – Chitosan Nanocomposites as Photocatalyst by Sol-Gel Method at Room Temperature - Imelda Fajriati; M Mudasir; Endang Tri Wahyuni (Universitas Jenderal Soedirman, 2017)
The synthesis of TiO2–chitosan nanocomposite photocatalyst using Titanium(IV)-Isopropoxide (TTIP) as precursors and chitosan as host material has been conducted. The synthesis was carried out using sol-gel method at room temperature and aging to grow crystal seeds and generate nanoparticles. The success of forming nano-sized anatase phase TiO2 nanocrystal was strongly influenced by the sol pH system during hydrolysis and the aging time. The effect of sol pH system and aging time to the crystallinity level and particle size were examined using X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM) and Diffuse Reflectance UV-Spectroscopy (DR-UV). The results showed that TiO2 produced in acidic pHs (pH 2-4) tended to have higher crystallinity level than that produced in weakly alkaline (pH > 6), which prone to be amorphous. The longer aging time (> 14 days) also tended to produce the amorphous phase. Furthermore, chitosan as a host material had a notable influence in determining the crystallinity level and particle size of TiO2 in TiO2–chitosan nanocomposite.